Uniformity of plantar pressure distributions: a novel metric for analysis. (4th May 2019) - Chandran, Avinash; Brown, Derek; DiPietro, Loretta; Danoff, Jerome
Abstract : Plantar pressure measurements, which present as bi-modal data, are used to examine how feet interact with different surfaces. Methods currently employed by researchers for comparing plantar pressure fail to describe the distribution of pressure over the entire foot. This study proposes the utilization of a novel metric, the Inverse Maximum Ratio (Λ'), that will allow researchers the ability to both quantify plantar pressure distribution using a single number, and utilize common methods of statistical hypothesis testing. Plantar pressure data from 17 subjects standing quiescently and using three under-foot conditions (bare foot, over-the-counter (OTC) insert under the foot, and customized foot insert (CFI) under the foot) were used to illustrate the utility of Λ' in this context. The results observed were consistent with expectations, in that the null condition (bare feet) presented with greatest non-uniformity in plantar pressure distribution, while the CFI condition presented with greatest uniformity. Based on these results, we note that Λ' can be used to expand upon current research that seeks to describe and compare the uniformity of plantar pressure distributions.